The Effect of Scrambled Picture towards Students’ Writing Skill - Haliza, Nur; Asilestari, Putri; Hardi, Vitri Anggraini (Universitas Pahlawan Tuanku Tambusai, 2024)
This research is motivated by the low writing skill of students in SMAN 2 Rumbio Jaya. This research aims to know the effect of Scrambled Picture toward students’ writing skill of tenth grade SMAN 2 Rumbio Jaya. The methodology in this research is quasy-experimental design consisting of an experimental class and control class. The experimental class consisted of 20 students and the control class consisted of 20 students. This research used purposive sampling as a sampling technique. The instrument used in this research was a test of writing. The data were analyzed by using the 25 SPSS program. Based on the result of the research, the average student score in the pre-test were 68.50 and 83.00 in the post-test. Data analysis showed a significance (2-tailed) 0.110.05, which means that Ha is accepted. It can be concluded that there is an effect of scrambled picture toward students’ writing skill of tenth grade SMAN 2 Rumbio Jaya.